Penerapan Latihan Dumbbell Arm Swing Terhadap Kecepatan Pukulan Forehand pada Cabang Olahraga Tenis Lapangan - Destadwi Rahmat Prasetyo; Alen Rismayadi; Yudi Nurcahya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effect of the dumbbell arm swing exercise on forehand stroke speed in tennis. The research method used was an experimental method with a pretest-posttest control group design. The study sample consisted of 20 students divided into two groups: an experimental group of 10 students who underwent dumbbell arm swing training, and a control group of 10 students who participated in regular training. The instrument used in this study was a forehand stroke speed test using a radar speed gun. Data analysis was performed using the Wilcoxon test to determine differences in pretest and posttest scores within each group, and the Mann–Whitney U test to determine differences in score gains between the two groups. The results of the study showed that the experimental group experienced a significant increase in forehand stroke speed after undergoing dumbbell arm swing training, with a significance value of 0.005 (p < 0.05). Meanwhile, the control group did not show a significant improvement, with a significance value of 0.105 (p > 0.05). The results of the Mann–Whitney U test on the gain scores showed an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a significant difference in improvement between the experimental group and the control group. Keywords: Dumbbell Arm Swing, Forehand Stroke Speed, Weight Training, Sports, Tennis